The Effectiveness Of Using Intens Book (Interactive English Book) Media In Learning English - Anandita, Septian Ragil; Muasyifah, Qonny; Afidah, Nurul; Agustina, Ulfa Wulan (LPPM Universitas KH.A.Wahab Hasbullah Jombang, 2024)
ABSTRACT This research is generally attempted to find the effectiveness of using INTENS BOOK (Interactive English Book) media in learning English for the class X-AKL-3 students at SMK PGRI 1 Jombang academic year 2022/2023. To know whether this media is effective or not, the researcher used pre-experimental research applied in X-AKL-3 class. The research had been done in six meetings that were designed: first meeting was for pre- test, 4 meetings were for treatments, and the last meeting was for post-test. As the quantitative method, the researcher analyzed the data by using the paired sample t-test. The result showed that there was siginificant difference on the student’s mean score of pre-test’s score was 66,12. Then in post-test, the mean score was 84,12. In other words, INTENS BOOK media is effective in learning English for advance learner, especially for first grade of senior high school students. Key words: Intens Book Media, Learning English ABSTRAK Penelitian ini secara umum bertujuan untuk mengetahui keefektivan penggunaan media INTENS BOOK (Interactive English Book) dalam pembelajaran bahasa Inggris siswa kelas X-AKL-3 di SMK PGRI 1 Jombang tahun pelajaran 2022/2023. Untuk mengetahui efektif atau tidaknya media ini, peneliti menggunakan penelitian pra- eksperimental yang diterapkan di kelas X-AKL-3. Penelitian ini dilaksanakan dalam enam pertemuan yang dirancang pertemuan pertama untuk pre-test, empat pertemuan untuk treatment, dan pertemuan terakhir untuk post-test. Sebagai metode kuantitatif, peneliti menganalisis data dengan menggunakan uji-t sampel berpasangan . hasil penelitian menunjukkan bahwa terdapat perbedaan yang signifikan pada nilai rata-rata siswa terhadap nilai pre-test sebesar 66,12. Kemudian pada post-test diperoleh nilai rata-rata sebesar 84,12 . Dengan kata lain, media INTENS BOOK efektif dalam pembelajaran bahasa Inggris bagi siswa tingkat lanjut, khususnya untuk siswa kelas satu sekolah menengah atas. Kata kunci: Media Intens Book, Pembelajaran Bahasa Inggris